Emerging from Emergence: Toward a Rethinking of the Recovery Story in Nine Contemporary Nonfiction Autism Narratives - Foss, Chris (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->In this paper I trace a welcome new trajectory within one of the fastest-growing subsets of illness/disability narrative over the last three decades— book-length accounts of living with autism spectrum disorders. My thesis is that one may observe a marked shift in how many of these writers now position themselves relative to the established pattern for such stories. According to the earlier model, the narrative moves inevitably toward the autistic individual’s recovery, or at least emergence, from his/her disability. More recently, most writers (from both first- and third-person points of view) have been rethinking the merits of such a teleology, often opting instead to insist upon their autism spectrum diagnoses as a fundamental aspect of their self-concept rather than as a hindrance to a more normal life and full self-realization.